Living with chronic kidney disease: future perspectives and prognostic needs of patients - a qualitative study - Jet Milders; Yvette Meuleman; Chava L. Ramspek; Willem Jan W. Bos; Wieneke M. Michels; Ype de Jong; Friedo W. Dekker; Merel van Diepen (BMC Nephrology)
Abstract Background Individualized prognostic information can help patients with chronic kidney disease (CKD) understand and prepare for their future, facilitating informed shared decision-making. While research has indicated that CKD patients want more information about their future, little is known about their specific prognostic needs. Therefore, this study aims to explore how patients with CKD perceive their future and what their prognostic needs are. Methods A survey was constructed with patient representatives, and distributed amongst adult CKD patients (all stages) through patient associations and healthcare professionals in two Dutch hospitals. Following an exploratory-descriptive qualitative approach, answers to four open-ended questions of 163 patients were analysed inductively using thematic analysis. Results Patients described a wide range of emotions when thinking about their future with CKD, including negative emotions like uncertainty, fear, sadness, and to a lesser extent, anger. However, some patients maintained emotional neutrality or described experiencing positive emotions like calmness, hope and trust. Additionally, patients had diverse prognostic needs, focusing on different topics like CKD treatment, kidney disease progression, self-management, symptoms, life expectancy and life participation. While most patients wanted more personalized prognostic information on these topics, some felt like they were already sufficiently informed about their future or preferred to live in the present moment. Conclusions Our findings show that CKD patients experience a wide variety of emotions regarding their future. Despite conversations about their future taking place in nephrological practice, there remain unmet questions regarding the future. These results underline the importance of adopting a personalized approach when discussing the future with CKD patients, acknowledging and taking the diverse emotional responses and individual preferences into account.